Contractual dualism, market power and informality - Arnab K. Basu; Nancy Chau; Ravi Kanbur (Institute for the Study of Labor (IZA), 2011)
Two stylized representations are often found in the academic and policy literature on informality and formality in developing countries. The first is that the informal (or unregulated) sector is more competitive than the formal (or regulated) sector. The second is that contract enforcement is easier in the formal sector than in the informal sector, precisely because the formal sector comes under the purview of state regulation. The basic contention of this paper is that these two representations are not compatible with each other. We develop a search-theoretic model of contractual dualism in the labor market where the inability to commit to contracts in the informal sector leads to employer market power in equilibrium, while an enforced minimum wage in the formal sector provides employers with a commitment technology but which reduces their market power in equilibrium. The contributions of this paper are three-fold. It (i) provides the micro-underpinnings for endogenous determination of employer market power in the formal and informal sectors due to contractual dualism in the two sectors, (ii) offers a unified and coherent setup whereby a host of salient features of developing country labor markets can be explained together, and (iii) places the original Stiglerian prescription of the optimal (unemployment minimizing) minimum wage in the broader context of labor markets where formal job creation is costly, and where formal employment, informal employment, and unemployment co-exist.
urn:nbn:de:101:1-201107283701
Keywords: J3; J6; O17; 330; contractual dualism; wage dualism; employer market power; informality